Cultural Diversity Evaluation in Educational Learning Groups. (2015) - Popescu, Anca-Diana; Suciu, Sorin; Borca, Cristina; Nodea, Adela; Ayotte, Lauren
Abstract: The objective of this article is to illustrate the cultural diversity evaluation in educational learning groups. Our research analyzes the intercultural competency of two groups of students studying in culturally diverse groups. The evaluation assessment was based on a set of tests measuring socio-cultural intelligence and group behaviour. Two learning groups composed of 68 subjects (experimental group) and 70 subjects (witness group) were used for the sample. In order to more suitably evaluate the learning groups' cultural diversity, the results obtained along with the educational performance of the learning groups (shown by their partial transcript of records) were taken into account. The research variables used were: age, nationality, residence (urban/rural), high school graduate and profile. Statistical processing was implemented using a specific IT platform developed in order to evaluate the cultural diversity of the groups and to send immediate feed-back to the subjects after completing each test.